ANALYSIS OF IMPLEMENTATION OF IJARAH MUNTAHIYA BITTAMLIK FINANCING IN ISLAM - Muhammad Asmawi; Nurmala Sari; Zulkarnain Lubis (El-Arbah: Jurnal Ekonomi, Bisnis Dan Perbankan Syariah, 2019)
Islamic banks have various forms of financing that are offered, one of which is the Ijarah vomiting Bittamlik (IMBT) financing. Ijarah Muntahiya Bittamlik financing is an ijarah transaction followed by the process of transferring ownership rights to the goods themselves or according to the agreement of both parties at the beginning of the contract. The existence of this form of financing has been around for a very long time, even since the emergence of Islamic banks in Indonesia. The main discussion in this study is about the terms and procedures for IMBT financing, the legal consequences that arise in IMBT financing.